Effectiveness of Health Management Information System in Selected Sub-Counties of Ryakarimira Town Council and Rubaya Sub-County. - Ayebare, Esther Loy (Kabale University, 2024)
This study aimed to assess the effectiveness of the Health Management Information System (HMIS) in health facilities within Ryakarimira Town Council and Rubaya Sub-County, Kabale District. The specific objectives included identifying standard tools for HMIS consolidation, evaluating the current effectiveness of HMIS, identifying associated challenges, and proposing strategies for improvement. The research utilized a cross-sectional design, incorporating both qualitative and quantitative approaches. Data were collected from 70 healthcare professionals in the selected sub-counties using questionnaires, interviews, and a thorough review of existing reports, policies, and other literature. The results indicated the availability of various tools for HMIS consolidation, categorized as tools for routine laboratory testing and referrals, equipment and logistics management, biosafety and biosecurity, microbiology and AMR surveillance, and periodic reporting. These tools included laboratory request forms, sample rejection forms, laboratory results report forms, sample referral forms, sample reception registers, daily activity registers, equipment inventory registers, equipment breakdown report forms, equipment breakdown registers, equipment maintenance logs, routine equipment service logs, order forms for HIV test kits and laboratory reagents, biosafety and biosecurity incident report forms, incident registers, microbiology request and results report forms, microbiology daily activity registers, national level periodic reports, WHO GLASS AMR reports, monthly facility-level laboratory reports, and quarterly facility-level laboratory reports. Most of the current tools were found effective in ensuring data consistency, accuracy, and overall efficiency, although some challenges were noted. These challenges included delays in data entry, limited resources for training, occasionally technical issues, infrastructure, and technological constraints, especially in remote areas, and concerns about data security and patient information privacy. The study concluded that the HMIS has been partially ineffective, highlighting the need for standardized tools, comprehensive training programs, and strategic investments to overcome challenges and enhance overall performance. The study recommended enhancing infrastructure, providing comprehensive training, investing in updated technology, and securing additional resources.